LANGUAGE EXPRESSION PATTERNS OF TALISMAN - Muhammad Nanang Qosim (Politeknik Negeri Jakarta, 2023)
Learning languages ​​is part of how understanding a language that is expressed orally or in writing. The disclosure of written representations describing the language of the talismans is a linguistic phenomenon. Linguistic theory is used to reveal the phenomenon of this talismanic language. The purpose of this study is to describe and explain, as well as to identify the language patterns of talismans used by the community. The method used in this study is descriptive-qualitative with descriptive analysis with note-taking techniques and sorting elements. The results of this study are (1) the linguistic elements of the mascot, namely nouns, adjectives, numbers, and sentences, and (2) the mascot model is divided by 2, namely the box model and the image model.